PERENCANAAN STRUKTUR BETON BERTULANG GEDUNG APARTEMEN BEJI DI PONTIANAK DENGAN MENGGUNAKAN SISTEM FLAT SLAB: PERENCANAAN STRUKTUR BETON BERTULANG GEDUNG APARTEMEN BEJI DI PONTIANAK DENGAN MENGGUNAKAN SISTEM FLAT SLAB - Maharani, Adinda Putri; Oktaviani, febri; Anggraini, Irene (RETENSI, 2024)
This planning aims to plan a reinforced concrete structure for the Beji Apartment Building in Pontianak by implementing a Flat Slab system. The research methods used include data collection, structural pre-design, structural modeling with the ETABS program, structural analysis, structural control, reinforcement design using Excel, and building dimension drawings with the AutoCAD program. The Flat Slab system was chosen because of its advantages in construction efficiency and spatial flexibility. The planning was carried out based on the SNI 2847:2019 standard concerning Procedures for Calculating Concrete Structures for Buildings. Structural analysis was carried out using ETABS and SpColumn software, which allows accurate load modeling and simulation. The results of the analysis show that the Flat Slab system is able to distribute the load evenly and provide adequate stability for multi-storey buildings. In addition, this system reduces the need for beams, thus adding to the aesthetics of the interior space of the building. From the results of the study, overall, the main structure of the building with the Flat Slab method (without beams) is able to withstand the loads that occur and is safe from punching shear failure which is something that can be risky in Flat Slab planning. Until now, there has been no use of Flat Slab structural system in Pontianak, so its application in this project can be a significant innovation in the development of construction in the region. The conclusion of this study is that the Flat Slab system is an efficient and effective choice for the construction of apartment buildings in areas with typical Pontianak soil conditions. Recommendations for further research are to test the performance of this system in earthquake load scenarios and evaluate the construction cost compared to other structural systems. Keywords: Planning, Apartment, Flat Slab, Drop Panel